Heart-type fatty acid binding protein is a novel prognostic marker in patients with non-ischaemic dilated cardiomyopathy. Issue 5 (30th December 2005) - Komamura, K; Sasaki, T; Hanatani, A; Kim, J; Hashimura, K; Ishida, Y; Ohkaru, Y; Asayama, K; Tanaka, T; Ogai, A; Nakatani, T; Kitamura, S; et al.
Abstract : Objective: To determine whether concentrations of heart-type fatty acid binding protein (H-FABP) measured before hospital discharge predict critical cardiac events in patients with idiopathic dilated cardiomyopathy (DCM). Patients: 92 consecutive patients with DCM were enrolled and followed up for four years. Main outcome measures: Serum concentrations of H-FABP, brain natriuretic peptide (BNP), cardiac troponin T before hospital discharge and survival rate. Results: 23 patients died of cardiac causes, received a left ventricular assist device or underwent heart transplantation during the four-year follow up. Univariate analyses showed that New York Heart Association functional class, heart rate, ejection fraction, serum H-FABP and plasma BNP were significant variables. According to multivariate analysis, serum H-FABP and plasma BNP concentrations were independent predictors of critical cardiac events. Cardiac troponin T before hospital discharge was not a predictor. The area under the receiver operating characteristic curve for death from critical cardiac events was similar between H-FABP and BNP. Patients with an H-FABP concentration at or above the median (⩾ 5.4 ng/ml) had a significantly lower survival rate than those below the median, according to analysis by log rank test (p < 0.0001). When combined with BNP concentration at or above the median (⩾ 138 pg/ml), H-FABP below the median predicted the worst prognosis among the combinations. Conclusions: The concentration of serum H-FABP before discharge from hospital may be an independent predictor for critical cardiac events in DCM.